2011
DOI: 10.4269/ajtmh.2011.11-0003
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hookworm Infection in Kintampo North Municipality, Ghana: Patterns of Malaria Coinfection, Anemia, and Albendazole Treatment Failure

Abstract: Abstract.A cross-sectional pilot study of hookworm infection was carried out among 292 subjects from 62 households in Kintampo North, Ghana. The overall prevalence of hookworm infection was 45%, peaking in those 11-20 years old (58.5%). In children, risk factors for hookworm infection included coinfection with malaria and increased serum immunoglobulin G reactivity to hookworm secretory antigens. Risk factors for infection in adults included poor nutritional status, not using a latrine, not wearing shoes, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
100
9

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(120 citation statements)
references
References 74 publications
7
100
9
Order By: Relevance
“…8 The possibility of benzimidazole resistance having arisen in human hookworms has been recently reviewed, 12 but there is still no indisputable evidence, although the efficacy of mebendazole in particular has been shown to have declined in some parts of the tropics, notably in Zanzibar, Vietnam, and Mali and instances of failure with albendazole have also been reported in Ghana. [13][14][15][16] Another trend in the current analysis worth commenting on was the age-related increase in the prevalence of B. hominis ( Figure 4B), which was much like that we reported earlier 2 and hence largely unaffected after the addition of data from the three most recent years. Because these data generate some concern over B. hominis infections among the elderly, we also compared data for the first period with the second and we found that there was an overall reduction in all age groups and the upward drift in prevalence was now only evident in the very oldest age class.…”
Section: Resultssupporting
confidence: 54%
“…8 The possibility of benzimidazole resistance having arisen in human hookworms has been recently reviewed, 12 but there is still no indisputable evidence, although the efficacy of mebendazole in particular has been shown to have declined in some parts of the tropics, notably in Zanzibar, Vietnam, and Mali and instances of failure with albendazole have also been reported in Ghana. [13][14][15][16] Another trend in the current analysis worth commenting on was the age-related increase in the prevalence of B. hominis ( Figure 4B), which was much like that we reported earlier 2 and hence largely unaffected after the addition of data from the three most recent years. Because these data generate some concern over B. hominis infections among the elderly, we also compared data for the first period with the second and we found that there was an overall reduction in all age groups and the upward drift in prevalence was now only evident in the very oldest age class.…”
Section: Resultssupporting
confidence: 54%
“…Seven studies 34,42,43,45,47,49,51 assessed hookworm only, while four studies 25,27,31,50 assessed A. lumbricoides only. Three studies described STH without speciation.…”
Section: 33mentioning
confidence: 99%
“…Three studies described STH without speciation. 35,36,46 Twelve studies 8,26,28,32,33,35,41,43,46,[49][50][51] assessed the impact of co-infection on anemia, using various measurements. Five studies 26,28,32,33,49 quantitatively reported anemia with the mean Hb level in various age groups and pregnant women.…”
Section: 33mentioning
confidence: 99%
See 1 more Smart Citation
“…30 We assessed confounding by a priori determined covariates: data collection round, sex, age, observed shoe wearing, and reported geophagy. 25,32 Because of sex-stratified findings from other trial outcomes, as a sub-analysis, we report sex-stratified estimates of effect. 18 All models controlled for cluster-level baseline worm infection levels.…”
Section: Methodsmentioning
confidence: 99%